Export Technological Sophistication of China: Measurement and Impact Factor - Peishan Fan (Discrete Dynamics in Nature and Society)
What matters for China’s future growth is not the volume of exports, but whether China will continue to enhance the export competitiveness of high-tech products. Using the export data of 25 countries from 1998 to 2019, this paper measures the export technological sophistication of machinery and transport equipment and constructs an empirical model to study the impact factors of export technological sophistication of machinery and transport equipment in China. The results show that the export technological sophistication is not high, although the export volume of machinery and transportation equipment is large. FDI, human capital, and the previous phase of export technological sophistication have a significant positive effect on the technological sophistication of export; however, the abundant natural resource has a significant negative effect. Finally, some countermeasures and suggestions are put forward based on the empirical results.